Catalytic performance of porous Yb2O3 sesquioxide. (3rd April 2021) - Aftab, Alina; Chagoya, Katerina; Felix, Alan; Blair, Richard; Orlovskaya, Nina
ABSTRACT: Porous Yb2 O3 ceramic (55%) was pressureless sintered at 900°C for four hours in air. The crystal structure of Yb2 O3 was confirmed to be cubic ( I a 3 ¯ ) with c = 10.43731 Å by neutron diffraction. The spectral vibrational signature of Yb2 O3 was also confirmed by micro-Raman spectroscopy. Yb2 O3 is an amphoteric oxide with both acid and base character, which presents the potential for producing different hydrocarbons when used as a Fischer–Tropsch (FT) catalyst. It was found that Yb2 O3 is indeed catalytically active and can be used to convert syngas (CO + H2 ) into useful hydrocarbons. Production of methane, ethene, and ethane was detected in the catalytic experiment performed at 500°C, but propane, propene, butane, and methanol were also detected in the experiment performed at 250°C. Hydrocarbons heavier than C4 were not observed. The limited data show deviation from a Flory–Schulz distribution suggesting additional surface processes are occurring beyond chain growth and termination.